Electrically programmable terahertz diatomic metamolecules for chiral optical control - Cong, Longqing (2020)
Optical chirality is central to many industrial photonic technologies including enantiomer identification, ellipsometry-based tomography, and spin multiplexing in optical communications. However, a substantial chiral response requires a threedimensional constituent, thereby making the morphology highly complex to realize structural reconfiguration. Moreover, an active reconfiguration demands intense dosage of external stimuli that pose a major limitation for on-chip integration. Here, we report a low bias, electrically programmable synthetic chiral paradigm with a remarkable reconfiguration among levorotatory, dextrorotatory, achiral, and racemic conformations. The switchable optical activity induced by the chiral conformations enables a transmission-type duplex spatial light modulator for terahertz single pixel imaging. The prototype delivers a new strategy towards reconfigurable stereoselective photonic applications and opens up avenues for on-chip programmable chiral devices with tremendous applications in biology, medicine, chemistry, and photonics.